2003
DOI: 10.1017/s1355617703910046
|View full text |Cite
|
Sign up to set email alerts
|

Ecological validity of a simplified version of the multiple errands shopping test

Abstract: Shallice and Burgess (1991) reported the utility of the Multiple Errands Test (MET) in discriminating executive deficits in three frontal lobe patients with preserved high IQ, who were otherwise unimpaired on tests of executive function. The aim of this study was to ascertain the value of a simplified version of the MET (MET-SV) for use with the range of people more routinely encountered in clinical practice. Main findings were as follows: 1) The test discriminated well between neurological patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
211
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(226 citation statements)
references
References 31 publications
8
211
1
5
Order By: Relevance
“…17,33,34 As for the number of subtasks, it could be linked to the inability to strategically plan, organize, and update current information, and to monitor ongoing performance. 33 A study by Alderman et al 35 with brain-injured participants showed 2 patterns of failure (number of rule breaks or failure to initiate tasks) in the simplified version of the Multiple Shopping Errands Test (The Multiple Shopping Errands Test, a ''real-life'' multitasking test carried out in a shopping center, requires the participant to buy specific things, obtain some information, be in a particular place at a particular time, and follow several rules while doing these things 35 ). These 2 patterns were associated with different executive problems in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,33,34 As for the number of subtasks, it could be linked to the inability to strategically plan, organize, and update current information, and to monitor ongoing performance. 33 A study by Alderman et al 35 with brain-injured participants showed 2 patterns of failure (number of rule breaks or failure to initiate tasks) in the simplified version of the Multiple Shopping Errands Test (The Multiple Shopping Errands Test, a ''real-life'' multitasking test carried out in a shopping center, requires the participant to buy specific things, obtain some information, be in a particular place at a particular time, and follow several rules while doing these things 35 ). These 2 patterns were associated with different executive problems in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were a bit different, insofar as the number of subtasks was not associated with apathy. However, the multitasking situation used by Alderman et al 35 is quite different from the MSET: it is conducted in a real environment, the rules are more concrete, and the number of subtasks is higher (12 subtasks). Indeed, the small number of subtasks to carry out on the MSET (only 6) means that it is probably not sensitive enough and reduces the interindividual variability.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, these tasks (and various modifications) have been utilized by a number of researchers to investigate executive functioning in normals and various patient populations (e.g., Alderman, Burgess, Knight, & Henman, 2003;Channon & Crawford, 1999;Duncan, Johnson, Swales, & Freer, 1997;Goel & Grafman, 2000;Goldstein, Bernard, Fenwick, Burgess, & McNeil, 1993;Jelicic, Henquet, Derix, & Jolles, 2001;Kafer & Hunter, 1997;Kliegel, McDaniel, & Einstein, 2000;Knight, Alderman, & Burgess, 2002;Levine, Dawson, Boutet, Schwartz, & Stuss, 2000a;Levine et al, in press Levine et al, 1998;Wilson et al, 1998), especially with an eye to rehabilitation planning (e.g., Levine et al, 2000b;Manly, Hawkins, Evans, Woldt, & Robertson, 2002). By now, there are consistent findings supporting the conclusion that these tasks are useful to characterize and quantify executive functioning deficits, and Burgess and his colleagues have made a convincing argument that "strategy application" types of task may be superior to traditional clinical neuropsychological tests (e.g., Wisconsin Card Sorting Test, WCST; Tower of London) at probing "real-world" deficits in executive functioning (Burgess et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is not clear if damage to the medial orbital and lower medial prefrontal sectors (the region that we have termed the ventromedial prefrontal cortices, or VMPC; see Tranel, Damasio, Denburg, & Bechara, 2005, for a precise description) is typical of patients who fail the SET and MET. In most previous studies, neuroanatomical issues were not addressed at all (e.g., Alderman et al, 2003;Burgess et al, 1998;Duncan et al, 1997;Jelicic et al, 2001;Kafer & Hunter, 1997;Kliegel et al, 2000;Knight et al, 2002;Wilson et al, 1998). Shallice and Burgess (1991) provided brief descriptions of the lesions in their original three cases, but other than mentioning frontal lobe damage, no specific details are provided, and it is not clear whether or not the VMPC was affected by the lesions (for two of these patients, a single computed tomography, CT, cut is provided in the recent review paper of Burgess et al (2006), but this does not clarify whether there is VMPC involvement).…”
Section: Introductionmentioning
confidence: 99%
“…The Multiple Errands Test (MET; Shallice & Burgess, 1991) is an example of a multitask assessment of executive functioning based on five demands of multitasking: (1) performing multiple but discrete tasks that vary in priority, complexity, and length; (2) managing interleaving and dovetailing tasks; (3) performing tasks without feedback; (4) dealing with interruptions, reprioritization, and rule changes; and (5) self-initiating task changes within the activity (Burgess, 2000). The many versions of the MET involve completing at least 10 unrelated tasks while complying with a series of rules in either a shopping mall or hospital lobby setting (Alderman, Burgess, Knight, & Henman, 2003;CuberosUrbano et al, 2013;Dawson et al, 2009;Morrison et al, 2013). Although the MET appears to assess "the central aspects of executive functioning in everyday life" (Frisch et al, 2012, p. 257), it has yet to be widely adopted in clinical practice because of site-specific validation requirements, time-intensive administration, and a lack of standardized scoring manuals specific to each site (Radomski & Morrison, 2014).…”
mentioning
confidence: 99%